Linguistic variation in China and its presence in literary works: analysis based on The Tea House - Yi, Wang (Sinología hispánica. China Studies Review, 2025)
Linguistic variation is a phenomenon present in almost all languages. In the case of China, with a vast territory and a large population, the dialect situation is complicated. In the present study, we intend to review the linguistic variation in China, as well as its presence in literature. With this objective, we have chosen The Tea House, a representative work of Beijing-featured novels. After a quantitative analysis, we confirmed that the presence of the geographical dialect is notable in the work and constitutes a resource for naturalness and character characterization.